2020
DOI: 10.18203/issn.2454-2156.intjscirep20205031
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with iron and folic acid supplementation and associated factors among pregnant women in Ethiopia: a systematic review and meta-analysis

Abstract: <p><strong>Background:</strong> Anaemia is one of the world’s leading cause of disability and the most serious global health issues. Globally about 38% (32 million) pregnant women are anaemic, from which 46.3% (9.2 million) are in Africa.</p><p><strong>Methods:</strong> Works of articles from PubMed, Medline and Google Scholar journal data-base were considered. Entirely articles allied to compliance and determinants of AFA supplementation were captured. The authors use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
3
2
0
Order By: Relevance
“…The present study supported a study conducted in four regions of Ethiopia 20 . Likewise, the current study findings agreed with several studies carried out in Northwest Ethiopia 50 , Aykal Town 30 , North Wollo Zone 53 , and Ethiopia 60 , 61 . The probable reason could be the awareness and educational status of the respondents.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study supported a study conducted in four regions of Ethiopia 20 . Likewise, the current study findings agreed with several studies carried out in Northwest Ethiopia 50 , Aykal Town 30 , North Wollo Zone 53 , and Ethiopia 60 , 61 . The probable reason could be the awareness and educational status of the respondents.…”
Section: Discussionsupporting
confidence: 92%
“…Pregnant women who had good knowledge of iron supplementation were 3.30 times more likely to be compliant with iron supplements as compared to pregnant women who had poor knowledge of iron supplementation. This current study was agreed with several studies carried out in Burji District 49 , West Dembia, Ethiopia 50 , Aykal town 30 , North Wollo zone 53 , Debre Tabor 52 , Debre Markos town 56 , Ethiopia 60 , 61 . Likewise, the current study supported studies conducted in SSA 63 , Kenya 65 , Nigeria 24 , Muntinlupa, and the Philippines 79 .…”
Section: Discussionsupporting
confidence: 91%
“…Pregnant women who started their rst ANC at greater than 16 weeks were 2.4 times more likely to non-Adherence to IFAS than their counterparts. This nding is in line with the study done in Central Ethiopia (43), Lay Armachiho Northwest Ethiopia (37), and at Hosanna Town of Southern Ethiopia (18). A study done at Tikur Anbessa specialized hospital showed that Gestational age at the rst ANC visit was signi cantly associated with adherence to IFAS.…”
Section: Discussionsupporting
confidence: 92%
“…According to WHO Adherence to Therapies: evidence for action, 19 adherence includes a wide range of behaviors related to health that go beyond taking prescribed medications. WHO also agrees to call adherence "the extent to which the patient follows medical instructions".…”
Section: Introductionmentioning
confidence: 99%
“…Providing counseling to pregnant women to improve adherence to taking blood-added supplements has resulted in significant benefits and impacts on changes in adherence of pregnant women in several studies that have been conducted in several countries. [17][18][19][20][21] Based on the background explained above, the researcher wants to undertake additional research on the subject of counseling intervention's impact on increasing adherence among pregnant women and those women planning to be pregnant, to determine whether counseling has this effect through literature studies.…”
Section: Introductionmentioning
confidence: 99%